THE INFLUENCE OF LOGICAL THINKING ABILITY, AND LEARNING PREPARATION ON MATHEMATICS LEARNING OUTCOMES THROUGH STUDENTS’ PARTICIPATION IN LEARNING - . Mirna (Universitas Negeri Makassar, 2015)
Students' learning ability is crucial to success in the learning process. Factors that influence student learning process include the ability to think logically, readiness to learn, and student participation in learning. This study aims to know and explain how much influence the ability of logical thinking, and readiness to learn the results of mathematics learning through the participation of students in learning in the seventh grade students of SMP Negeri In the District Pitumpanua Wajo. This research is an ex-post facto research that is causality. The population in this research is 362 students of Class VIII SMP Negeri in Pitumpanua Subdistrict Wajo Regency year 2015/2016. The sample of 157 students studied using proportional random sampling. Instruments used consisted of logical thinking ability test, questionnaire of learning readiness, student participation questionnaire in learning, and test of mathematics learning result. Data analysis with descriptive statistics and inferential statistical analysis (path analysis). The result of the research shows that (1) Most of VIII grade students of SMP Negeri in Pitumpanua Subdistrict Wajo have the ability to think logically in learning mathematics with medium category, readiness of student learning in mathematics with enough category ready, student participation in learning in learning mathematics with categoryActive, and the results of learning mathematics with the category of being. (2) The variables that have significant influence that is, the readiness of learning has a direct effect on the learning outcomes, the readiness of learning has a direct effect on the participation of students in learning, the readiness of learning has an indirect effect through the participation of students in the learning, and the participation of the students in the learning directly influence the learning outcomes mathematics. (3) Influence variable is insignificant that is, ability of logical thinking have direct effect to result of learning, logical thinking ability have direct effect to student participation in learning, and ability of logical thinking have an indirect effect to result of learning of mathematics through student participation in learning with level of kesignifikanan